Post-Traumatic Stress Disorder As Reflected On Cara Hoffman Be Safe I Love You Novel - Pratiwi Sosalia M.R.; Sudirman Maca; Asyrafunnisa Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2023)
The aims of this research are to identify the types of Post – Traumatic Stress Disorder as well as to find out the impacts caused by Post – Traumatic Stress Disorder that are contained in Be Safe I Love You novel. In this research the writer applied qualitative descriptive methods and theory by Sigmund Freud to analyse the phases of Post – Traumatic Stress Disorder in the novel Be Safe I Love You. The result shows that there are types and impacts of post-traumatic stress disorder contain in Cara Hoffman's Be Safe I Love You novel base on Sigmund Freud's theory, the writer find that there are two types of post-traumatic stress disorder, namely acute stress disorder and post-traumatic stress disorder without complications. Uncomplicated post-traumatic stress disorder is the most dominant type of post-traumatic stress disorder find in the novel. There are 4 effects of post-traumatic stress disorder find in the novel, namely hallucinations, mood swings, irritability, insomnia.